1989
DOI: 10.1007/bf02823696
|View full text |Cite
|
Sign up to set email alerts
|

Immunological state of adult germfree miniature minnesota pigs

Abstract: Fundamental hematological and immunological data were obtained on sexually mature germfree miniature pigs fed, after the milk diet period, with cereal-type diet sterilized by gamma-radiation, and were compared with data of control conventional animals. Germfree adult pigs had a lower count of peripheral blood leukocytes with a lower percentage of neutrophil granulocytes and without any younger forms, a lower total serum protein level with a negligible amount of gamma and alpha 2 globulin fractions and a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…While blood cell counts are mainly influenced by the presence or absence of pathogens, elevated total protein levels in serum are considered to be influenced by stimulation with food antigens [20]. The observed significant RBC levels in the Aachen minipig, and subsequently the derived mean corpuscular hemoglobin and mean corpuscular volume levels, are in the physiological range and comparable to other breeds of minipigs and domestic pigs [21,22,23].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While blood cell counts are mainly influenced by the presence or absence of pathogens, elevated total protein levels in serum are considered to be influenced by stimulation with food antigens [20]. The observed significant RBC levels in the Aachen minipig, and subsequently the derived mean corpuscular hemoglobin and mean corpuscular volume levels, are in the physiological range and comparable to other breeds of minipigs and domestic pigs [21,22,23].…”
Section: Discussionmentioning
confidence: 96%
“…It has been described that the higher exposure to pathogens or antigens in conventional husbandry results in elevated WBC, neutrophil counts, and clinical chemistry parameters such as albumin compared to gnotobiotic or SPF-housed pigs [20]. While blood cell counts are mainly influenced by the presence or absence of pathogens, elevated total protein levels in serum are considered to be influenced by stimulation with food antigens [20].…”
Section: Discussionmentioning
confidence: 99%
“…These studies concluded that piglets are immunocompetent at birth [22], albeit with a largely 'immature' immune system that has not been previously in contact with antigens, resulting in a primary immune response, a less developed mucosal immune response and lower repertoire diversity than in adults [182]. Piglets also constitute a unique material for studying the development of the postnatal immune response [120] without any other antigenic stimulus, since they can be reared in germ-free [179,222] and antigen-free environments [108,129]. However, certain characteristics of the porcine lymphoid system may affect the immune system, and thus require the development of appropriate cellular and molecular reagents and tools [184].…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, there have been few reports about the blood biochemistry for specific pathogen-free (SPF) miniature pigs, although simple hematology tests have been conducted in germ-free Minnesota miniature pigs [9,10]. In addition, normal values for blood biochemistry may be age-dependent, and only age-related changes in platelet activity have previously been reported [11,12].…”
mentioning
confidence: 99%